ОЧНА МАЗЬ - Сотнікова, Олена Петрівна; Красновид, Тетяна Андріївна; Абрамова, Ганна Борисівна; Салдан, Вікторія Йосипівна; Лотош, Тамара Дмитрівна; Фесюнова, Галина Степанівна; Соколова, Броніслава Ніфонтівна; Іванов, Валерій Іванович (My University, 2012)
Очна мазь містить хлоридну мазь та пелоїдодистилят.
OPHTHALMIC OINTMENT